A facile electrochemical approach to fabricate a nanoporous gold film electrode and its electrocatalytic activity towards dissolved oxygen reduction. Issue 43 (8th October 2015) - Sukeri, Anandhakumar; Saravia, Lucas Patricio Hernández; Bertotti, Mauro
Abstract : NPGF electrode was fabricated in absence of alloys, templates & chemical reducing agents and its electrocatalytic activity towards DO reduction was achieved at very low overpotential with enhanced sensitivity. Abstract : A nanoporous gold film (NPGF) was prepared onto a gold electrode surface using a facile and green electrochemical approach via anodization at 2.0 V in 0.5 mol L −1 H2 SO4 . The as-synthesized NPGF electrode showed superior electrocatalytic activity towards dissolved oxygen reduction at a low overpotential (−0.045 V) along with 2-fold enhanced sensitivity.